174k views
2 votes
Find the LCM of m^2 - 4m - 5 and m^2 + 8m + 7

User Prisco
by
5.2k points

1 Answer

5 votes

Answer:

LCM=(m+1)(m-5)(m+7)

Explanation:

Given expressions are
m^2-4m-5 and
m^2+8m+7.

To find the LCM, first we need to find factors of both expressions.


m^2-4m-5


=m^2+1m-5m-5


=m(m+1)-5(m+1)


=(m+1)(m-5)

Similarly factor other expression


m^2+8m+7


=(m+1)(m+7)

Common factor in both is (m+1)

bring down remaining non-common factors.

So LCM=(m+1)(m-5)(m+7)

User MikeQ
by
5.3k points